Evolution of guanylate binding protein genes shows a remarkable variability within bats (Chiroptera) - Pinheiro, Ana; Borges, J. Ricardo; Côrte-Real, João Vasco; Esteves, Pedro J. (Frontiers in Immunology, 2024)
Background: GBPs (guanylate binding proteins), an evolutionary ancient protein family, play a key role in the host's innate immune response against bacterial, parasitic and viral infections. In Humans, seven GBP genes have been described (GBP1-7). Despite the interest these proteins have received over the last years, evolutionary studies have only been performed in primates, Tupaia and rodents. These have shown a pattern of gene gain and loss in each family, indicative of the birth-and-death evolution process.Results: In this study, we analysed the evolution of this gene cluster in several bat species, belonging to the Yangochiroptera and Yinpterochiroptera sub-orders. Detailed analysis shows a conserved synteny and a gene expansion and loss history. Phylogenetic analysis showed that bats have GBPs 1,2 and 4-6. GBP2 has been lost in several bat families, being present only in Hipposideidae and Pteropodidae. GBPs1, 4 and 5 are present mostly as single-copy genes in all families but have suffered duplication events, particularly in Myotis myotis and Eptesicus fuscus. Most interestingly, we demonstrate that GBP6 duplicated in a Chiroptera ancestor species Bats GBPs evolution originating two genes, which we named GBP6a and GBP6b, with different subsequent evolutionary histories. GBP6a underwent several duplication events in all families while GBP6b is present as a single copy gene and has been lost in Pteropodidae, Miniopteridae and Desmodus rotundus, a Phyllostomidae. With 15 GBP genes, Myotis myotis and Eptesicus fuscus stand out as having far more copies than all other studied bat species. Antagonistically, Pteropodidae have the lowest number of GBP genes in bats.Bats are important reservoirs of viruses, many of which have become zoonotic diseases in the last decades. Further functional studies on bats GBPs will help elucidate their function, evolutionary history, and the role of bats as virus reservoirs.